Effect of target composition on proton energy spectra in ultraintense laser-solid interactions. - Robinson, A; Bell, A; Kingham, R (2006)
We study how the proton density in a target irradiated by an ultraintense laser affects the proton spectrum, with analytical models and Vlasov simulations. A low relative proton density gives rise to peaks in the energy spectrum. Furthermore, a target with the protons confined to a thin, low density layer produces a quasimonoenergetic spectrum. This is a simple technique for producing proton beams with a narrow energy spread for proton radiography of laser-plasma interactions.